Intraoperative hypotension in non-emergency decompression surgery for cervical spondylosis: The role of chronic arterial hypertension - Chiang, Ting-Yun; Wang, Yen-Kai; Huang, Wen-Cheng; Huang, Shiang-Suo; Chu, Ya-Chun (Frontiers in Medicine, 2022)
Background Cervical spondylotic myelopathy and chronic hypertension show a cause-effect relationship. Hypertension increases cardiovascular risk and is associated with intraoperative hypotension. We aimed to evaluate intraoperative hypotension in patients undergoing non-emergency decompression surgery for cervical spondylosis and its association with clinical myelopathy and chronic arterial hypertension. Methods This retrospective cohort study used healthcare data of adult patients undergoing cervical spine surgeries at Taipei Veterans General Hospital from 2015 to 2019. The primary outcomes were the incidence of intraoperative hypotension and predictive factors, and the secondary outcomes were the association of intraoperative hypotension and postoperative adverse outcomes in the surgical population. Results Among the 1833 patients analyzed, 795 (43.4%) required vasopressor treatment and 342 (18.7%) showed persistent hypotension. Factors independent associated with hypotension after anesthetic induction were age (odds ratio [OR], 1.15; 95% confidence interval [CI], 1.07−1.23 per 5 years, P<0.001), male sex (OR, 1.63; 95% CI, 1.21−2.19, P<0.001), chronic hypertension (OR, 1.77; 95% CI, 1.32−2.38, P<0.001), upper cervical spine level C0-2 treated (OR, 3.04; 95% CI, 1.92−4.84, P<0.001 vs. C3-T1), and increased number of spine segments treated (OR, 1.43; 95% CI 1.26−1.63, P<0.001). Patients who developed intraoperative hypotension experienced more acute postoperative kidney injury (OR, 7.90; 95% CI, 2.34–26.63, P<0.001), greater need for intensive care (OR, 1.80; 95% CI, 1.24–2.60, P=0.002), and longer admission after surgery (1.09 days longer, 95% CI 0.06−2.12, P=0.038). Conclusions Intraoperative hypotension is common even in non-emergency cervical spine surgery. A history of hypertension independently predicted intraoperative hypotension. Prompt assessments for identifiable features can help ameliorate intraoperative hypotension.